Preclinical evaluation of the potential for cytochrome P450 inhibition and induction of the selective ALK inhibitor, alectinib. (2nd December 2017) - Sekiguchi, Nobuo; Nagao, Shunsuke; Takanashi, Kenji; Kato, Motohiro; Kaneko, Akihisa; Morita, Keiichi; Shindoh, Hidetoshi; Ishigai, Masaki
Abstract: 1. A novel selective anaplastic lymphoma kinase (ALK) inhibitor, alectinib, has shown remarkable efficacy and safety in patients with ALK-positive non-small-cell lung cancer (NSCLC). The purpose of this study was to evaluate in vitro the potential to inhibit and induce cytochrome P450 (CYP) isoforms for alectinib and its major metabolite M4. 2. Alectinib and M4 did not show the meaningful direct inhibition of six major CYP isoforms (CYP1A2, 2B6, 2C9, 2C19, 2D6 and 3A4) in human liver microsomes (HLM). Alectinib, but not M4, competitively inhibited CYP2C8, by which few marketed drugs are exclusively metabolized, with an inhibition constant of 1.98 μM. 3. Out of the seven CYP isoforms in HLM, alectinib and M4 showed time-dependent inhibition (TDI) of only CYP3A4, which suggests low TDI potential due to low inactivation efficiency. 4. Alectinib exhibited quite smaller induction of mRNA expression of CYP1A2, 2B6 and 3A4 genes in human hepatocytes compared to the respective positive controls, suggesting a low potential of enzyme induction. 5. In summary, the risk of alectinib causing drug-drug interactions with coadministered drugs is expected to be low due to the weak potential of CYP inhibition and induction estimated in the preclinical studies.